Pragmatisme Hukum dan Sunset Review: Menuju Proses Legislasi yang Responsif dan Akuntabel - Xavier Nugraha; Jeniffer Avrillya Wibisono; Gwyneth Eugenia Keisya Howard; Angelica Novia Walasondakh (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Indonesian legislation is frequently enacted in disregard of essential foundation, rendering the legislative process merely formalistic. This results in compromised quality and a lack of systematic evaluation regarding regulatory effectiveness, contradicting legal pragmatism which prioritizes practical utility and social impact. To bridge this gap, implementing a Sunset Review mechanism is highly necessary in Indonesia. This mechanism mandates the legislature to periodically review regulations within a spesific timeframe to determine their continued validity. Consequently, this ensures that Indonesia’s legal instruments remain responsive, accountable, and adaptive to societal dynamics.